SENSITIVITY AND SPECIFICITY OF PROSTATIC BIOPSY RESULT BASED ON PROSTATE VOLUME - Pitoyo, Joko; Safriadi, Ferry (Indonesian Journal of Urology, 2014)
Objective: To compare the sensitivity and specificity of both types of prostate biopsies, between 6 core biopsy/sextant biopsy with volume based biopsy prostate. Material & method: The subjects were patients that have been performed prostate biopsy in Hasan Sadikin Hospital in 2006 – 2010. The data was divided into two groups, the group A (before 2009) 327 patients had performed 6 cores biopsy, group B (after 2009), the biopsy was performed based on prostate volume (volume < 40 cc : 8 cores, volume 40-60 cc : 10 coresand volume > 60 cc : 12 cores). Biopsy results confirmed by definitive results from surgery, then analyzed specificity and sensitivity between two groups. The analytical statistic test using unpaired T test and Levene’s test. Results: There were 654 patients divided in two groups. The data in both groups were similar based on analytical statistic test using unpaired t test (p = 0.28) and the data was in normal distribution (Levene’s test = p > 0.05). The group A, mean age 67.4 years, mean prostate volume 32.53 cc and mean PSA levels 29.89 ng/dl and at group B, mean age 66.7 years, mean prostate volume 30.89 cc and mean PSA levels 16.92 ng/dl. Volume based cores method in prostate biopsy have higher sensitivity and specificity compared with 6 core biopsy (97.5% vs 94.0%) and (92.2% vs 77.8%). Conclusion: The sensitivity and specificity of prostate biopsy was increased in volume based cores compared to 6 cores biopsy. Keywords: Prostate biopsy, volume based.